Exploring the soothing power of endorphin massage as a natural pain reliever for pregnant women - Dewanti, Amelia Cahya; Rohmayanti, Rohmayanti; Rahayu, Heni Setyowati Esti (Universitas Muhammadiyah Magelang, 2024)
Many pregnant women experience discomfort and pain in various body parts, particularly in the back, as their uterus and fetus grow. Endorphin massage, a gentle touch therapy, can provide relief and comfort for pregnant women approaching delivery. This study aims to overview nursing care for third-trimester pregnant women experiencing acute pain issues through the application of endorphin massage. The research utilized a case study design with a consecutive sampling technique. Participants included third-trimester pregnant women suffering from back pain, who received 15 minutes of endorphin massage once daily in the afternoon. Results indicate that the application of endorphin massage significantly reduced the pain scale for the participants, decreasing from an average of 8 to 1 over six consecutive visits. This suggests that endorphin massage effectively alleviates the intensity of back pain in third-trimester pregnant women. Keywords: Acute pain; innovation in maternity care; endorphin massage; pregnant women; treatment